(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
The national health insurance system was developed through the Social Security Organizing Agency (BPJS) which is divided into Health Insurance and Employment Guarantee. Health Insurance aims to ensure that participants benefit from health care and protection in meeting basic health needs. But in practice, some hospitals reject BPJS Health patients on the grounds of full rooms, as experienced by Mr. Nana’s family at Permata Hijau Hospital, Jakarta. This study is titled "Handling Emergency Patients Referenced to Permata Hijau Hospital Based on Law Number 36 Year 2009 Concerning Health (Case Study of Mr. Nana’s Family Patients)" with the formulation of the problem How is the application of referral procedures for emergency patients at Permata Green Hospital? and What are the legal consequences for health service facilities that do not provide first aid (case study of the family of Mr. Nana)? This research uses empirical research methods. The results showed that the referral procedure at Permata Hijau Hospital was not in accordance with applicable regulations. The legal consequences for facilities that do not provide assistance may be subject to a maximum imprisonment of 2 (two) years and a maximum fine of Rp.200,000,000.00 (two hundred million rupiah).